EVALUASI KEBIJAKAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DAN DAMPAK PERTAMBANGAN BAHAN GALIAN BATUAN (STUDI KASUS) DI KECAMATAN LABUAN KABUPATEN DONGGALA - Jinurain, Jinurain (Katalogis, 2017)
This study aimed to analyze the policy evaluation of corporate social responsibility and the impact the management of mineral mining rock in Donggala District of Labuan pursuant Company Law No. 40 of 2007 on corporate social responsibility. The method used is descriptive qualitative method of observation, interviews and documentation. Mechanical election informants purposive sampling as many as 10 people. The theory used is Brigman and Davis in Bajuri and Yuwono (2003: 140-141) that is input, process, output and outcome that the study results showed that the Social Responsibility Company or known as (CSR) not run optimally and do not reflect the ideal conditions in accordance with the policies and performance expectations of the public in accordance with the regulations that govern it, with some of the aspects that influence, among others: : 1) .Input, related support resources that have adequate human resources and money. 2) .it, in the implementation of the indicator right on target and to still not optimal. 3). Output, an indicator of policies for the less give effect to the public good. 4). Outcome that the company's social policy is less a real impact to the community as well as the impact of the environment around them is the loss of clean water sources, erosion, and dust in the mining area in the district of Donggala Labuan.